Management control system of asnaf entrepreneurship programs: a focus on belief control - Mohamed, Nor Hayati Samba; Wan Ahmad, Wan Noraswaniaty; Abdullatiff, Nik Kamaruzaman (Universiti Teknologi MARA, Kelantan, 2018)
Besides a permanent assistance to incapable asnaf, zakat can also be given as temporary assistance to productive zakat recipients. The establishment of entrepreneurship programs for selected asnaf is one of the initiative done by zakat institutions in order to help asnaf independently earn their living and break free from zakat. This qualitative study focuses on the entrepreneurship programs by two zakat institutions namely Zakat Institution A (ZIA) and Zakat Institution B (ZIB) where some portions of zakat collected are distributed productively to selected asnaf in the form of business capital. There’s an increase expectation towards zakat institutions in improving the management of zakat fund. To some extent, zakat organizations are expected to be managed like a private corporation which includes implementation of formal management control system (MCS) in its operation. The objective of the study is to explain the impact of MCS in the entrepreneurship program set up for asnaf. A total of seven interviews among officers in charge of entrepreneurship programs and asnaf in both organizations were carried out. Levers of control (LOC) have been used as the applied framework representing MCS. The study only focuses on one LOC which is Belief Control. It was found that belief on the importance of religiosity and belief on the importance of entrepreneurship program has an association with the success of asnaf entrepreneurs. This study is intended to contribute to the future improvement plans of other entrepreneurship programs for the poor and needy especially by other zakat institutions. It includes implementation of Belief Controls expected to influence the success of entrepreneurship programs. With such improvements, it will indirectly create confidence amongst zakat payers in Malaysia and Muslims as a whole.